Cost of Treating Coronavirus Disease 2019 (COVID-19) Patients in Hospitals and Influencing Factors: A Systematic Literature Review - Henri Azis; Atik Nurwahyuni; Firdinand (HM Publisher, 2022)
Background: Increasing beds for COVID-19 patients is not a simple matter for hospitals because hospitals cannot directly increase the number of existing beds due to limited facilities, infrastructure, equipment, and resources. Careful calculations are needed in terms of preparing the room and treating COVID patients, especially the estimated costs needed to treat COVID patients in the hospital. This expenditure is important so that it can be an illustration of the hospital how much expenditure is needed. This study aimed to determine the number of costs incurred for treating COVID-19 patients in hospitals and the factors that influence these costs. Methods: This study was conducted by systematic literature review using the PRISMA statement conducted May-June 2021. An article search was conducted on Pubmed, Scopus, Proquest, and Google Scholar with the inclusion criteria, namely research related to the cost of treating COVID-19 patients in hospitals and the factors that influence the amount of these costs. Results: A systematic search obtained six articles. Studies vary greatly in study design and perspective included in the cost category. Estimated costs for COVID-19 care range from 63/day to 2,990/day. Factors that affect the cost of care include age, previous medical history, degree of infection or severity of COVID-19, length of stay, place of care, and need for a ventilator. Conclusion: There is a considerable economic burden associated with the incident of COVID-19. Several factors affect the cost of COVID-19, namely the length of the treatment period and the need for intensive rooms and ventilators.